Exploring the role of health applications in promoting health among older adults: a scoping review protocol - Angélica Baptista Silva; Maria Tereza Leal; Sergio Ricardo Ferreira Sindico; Mercedes Serrano-Miguel; Helena Maria Almeida Macedo Loureiro (BMJ Open, 2024)
Introduction Evidence on the use of health apps to support healthcare and promote the health of individuals aged 55 and older is limited. Older adults face challenges with literacy, usability and accessibility of digital tools. This scoping review aims to explore how digital health apps promote healthy living and self-empowerment while identifying successful applications for older adultsMethods and analysis This study will adopt the JBI methodology for scoping reviews, guided by the (Population, Concept, Context) framework. The results will be comprehensively reported in the final scoping review and illustrated using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews. The inclusion criteria include studies from 2016 to 2024 that investigate the use of health applications within healthcare services for older adults.Ethics and dissemination Ethical approval is not required for this scoping review. The findings will highlight potential directions for future research and improve knowledge among professionals, researchers and the public. The results will be published in a peer-reviewed journal and disseminated through professional networks. Data will be available from the Open Science Framework.